Clinico-radiological profile of abdominal tuberculosis in HIV/AIDS patients-a study from rural central India - Wafai, Nisar A.; Yadav, Sudhir K.; Singh, Prem S.; Kumar, Manoj; Singh, Prafulla K.; Sharma, Himanshu; Pious, Tony; Gautam, Rajesh K. (International Journal of Research in Medical Sciences, 2017)
Background: One of the major challenge of present era is dual epidemic of HIV/AIDS and tuberculosis. With immunosuppression, risk of opportunistic diseases increases in these patients and tuberculosis is most common opportunistic infection. The prevalence of abdominal tuberculosis seems to be rising, particularly due to increasing prevalence of HIV infection. The diagnosis of abdominal tuberculosis can often be difficult and it remains underdiagnosed, in view of its nonspecific manifestations. The investigations involved in its diagnosis are expensive and time consuming, however, ultrasonography (USG) is an affordable, non-invasive and widely available modality which can be of help in the diagnosis of abdominal tuberculosis. Therefore, this study was undertaken to evaluate clinical and USG finding among Abdominal Tuberculosis patients with HIV/AIDS. Methods: After informed consent, patients underwent thorough history taking and clinical examination followed by high quality USG abdomen and other biochemical and haematological tests including CD4 count. Follow up USG abdomen was done at time of completion of course of ATT and data was analysed. Results: 45 were found to have abdominal tuberculosis. Of these patients, 31(68.9%) were male and 14 (31.1%) were female. Mean age of HIV-abdominal TB was 34.27±9.66 years. most common symptoms were weight loss 41(91.1%), loss of appetite 38(84.4%), fever 32(71.1%), generalized weakness 30(66.7%) and abdominal pain 27(60.0%). On USG abdomen, intraabdominal lymphadenopathy was most common finding found in 44(97.8%). Average size of enlarged lymph node was 3.1+-1.0 cm. Mesenteric lymphnodes were enlarge in 40(88.89%), paraaortic 8(17.78%), retroperitoneal 4(8.89%) while peripancreatic and porta hepatic in 3(6.67%). splenomegaly was noted in 14(31.1%) cases. Hepatomegaly was found in 6 cases, who all were male. Ascites was evident in 5(11.1%) patients. Extensive involvement, defined as involvement of two or more intraabdominal sites, was found 24(53.3%) cases. There was no statistically significant difference found among these USG findings and CD4 count. Conclusions: The findings of lymphadenopathy (size>15mm) and hypoechoic/necrotic echotexture, hepatosplenomegaly with hypoechoic lesions in ultrasonography are suggestive of abdominal tuberculosis in HIV infected patients with unexplained nonspecific symptoms and low CD4 count. However, above findings are not standardized and inability to confirm the diagnosis of tuberculosis by direct microscopy and culture is the limitation of this study. Ultrasonography is an affordable, widely available, non-invasive imaging modality which may be optimally utilized for the diagnosis of abdominal tuberculosis in HIV infected patients, especially in the rural setup where microbiological and other sophisticated radiological investigations have limited availability.